2015
DOI: 10.1103/physrevapplied.3.054001
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Midinfrared On-Chip Electrical Generation of Graphene Plasmons by Inelastic Electron Tunneling Excitation

Abstract: Inelastic electron tunneling provides a low-energy pathway for the excitation of surface plasmons and light emission. We theoretically investigate tunnel junctions based on metals and graphene. We show that graphene is potentially a highly efficient material for tunneling excitation of plasmons because of its narrow plasmon linewidths, strong emission, and large tunability in the midinfrared wavelength regime. Compared to gold and silver, the enhancement can be up to 10 times for similar wavelengths and up to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Interestingly, the high rates of GP emission also conform to research of the reverse process—of plasmons enhancing and controlling the emission of hot carriers—that is also found to be particularly strong in graphene 58 59 . This might reveal unexplored relations between ČE and other novel ideas of graphene-based radiation sources that are based on different physical principles 60 61 62 63 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the high rates of GP emission also conform to research of the reverse process—of plasmons enhancing and controlling the emission of hot carriers—that is also found to be particularly strong in graphene 58 59 . This might reveal unexplored relations between ČE and other novel ideas of graphene-based radiation sources that are based on different physical principles 60 61 62 63 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Understandably, focused beams in electron microscopes have been the probe of choice to excite and map plasmons with nanometer spatial resolution via the recorded electron energy-loss and cathodoluminescence signals . Electron tunneling has been considered for a long time as a mechanism for the excitation of plasmons, while electron injection by tunneling from conducting tips into metallic structures has also been demonstrated to produce efficient plasmon excitation. More dedicated designs have incorporated emitting devices in which the generated light directly couples to the plasmon near field. , A recent theoretical study has shown that plasmons can boost tunneling across an insulator separating two graphene layers, with potential use as a plasmon-gain device, while a similar structure has been experimentally used for the electrical generation of THz radiation . Additionally, evidence of radiative gap-plasmon decay has been experimentally obtained, associated with hot electron tunneling under external illumination …”
mentioning
confidence: 99%
“…In particular, there is growing interest in the field of graphene plasmonics due to its attractive tight optical confinement property, which allows extreme scaling of nanophotonic devices as well as increased light-matter interaction in the graphene medium. 1 In these recent few years, there were many theoretical and experimental demonstrations of graphene-based plasmonic photodetectors, [2][3][4] switches and modulators, 5-7 logic gates, 8,9 light sources, [10][11][12][13] and polarizers and sensors. [14][15][16][17] One of the major research areas in graphene is nonlinear photonics, which has seen applications in saturable absorbers, 18 nonlinear switching and solitons, [19][20][21][22] supercontinuum generation, 23 four-wave mixing, 24 and third-harmonic generation.…”
mentioning
confidence: 99%